Multi-Year Concentrations, Health Risk, and Source Identification, of Air Toxics in the Venice Lagoon - Morabito, Elisa; Gregoris, Elena; Belosi, Franco; Contini, Daniele; Cesari, Daniela; Gambaro, Andrea (Frontiers in Environmental Science, 2020)
This work presents and discusses the results of measurements of PM10 concentrations and of its content in metals, obtained in three different sites of the Venice lagoon area where the construction of the MOSE (Modulo Sperimentale Elettromeccanico-Electromechanical Experimental Module) mobile dams was going on. Measurements were taken between 2010 and 2015 and the spatial and seasonal variability of metals and PM10 concentration were discussed. The aim of the work is to get information on the air quality in the lagoon area related to the presence of toxic metals in particulate matter produced by construction activities. Additional measurements of PAHs concentration in gas and particle phases, and the related health risk assessment, were carried out in two out of the three sites, in order to enhance the knowledge about the air quality near the construction yards. Diagnostic ratios have been calculated for the purpose of investigating the PAH sources of the area. PM10 was collected using low volume sequential aerosol samplers, with quartz filters carefully decontaminated in an atmosphere-controlled laboratory. Inorganic elements (V, Cr, Fe, Co, Ni, Cu, Zn, As, Mo, Cd, Sb, Tl, and Pb) in PM10 samples were measured by ICP-MS. Samples for PAH analyses were collected using a high-volume air sampler that allows to sample both gaseous and particulate PAH simultaneously. Gaseous PAHs were collected on pre-cleaned polyurethane foams and particulate PAHs on pre-combusted quartz fiber filters. Samples for PAHs determinations were analyzed by GC-HRMS. Results showed limited differences in metals' and PAHs' concentrations between the sites, indicating a relatively homogeneous spatial distribution of metals in PM10 and PAHs in the Venice lagoon area. Temporal trends furthermore give indication of a slight decrease in PAHs and PM10 concentration in Punta Sabbioni and in its content of Pb, Zn, and Sb. The health risk assessment showed that congeners that most contributed to the carcinogenicity of the mixture were benzo(a)pyrene e dibenzo(A,H)anthracene, mainly in the particulate phase. The study provides an important multi-years trend of chemical characterization of the Venice lagoon aerosol and about air quality in terms of toxic chemicals concentration in the atmosphere.